Short-Term Outcome of Intracranial Aneurysms Treated with Polyglycolic Acid/Lactide Copolymer–Coated Coils Compared to Historical Controls Treated with Bare Platinum Coils: A Single-Center Experience - Kang, Hyun-Seung; Han, Moon Hee; Kwon, Bae Ju; Kwon, O-Ki; Kim, Sung Hyun; Choi, Seung Hong; Chang, Kee-Hyun (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Aneurysm recanalization is an innate problem in endovascular treatment of aneurysms with coils. A coated coil system, covered with a bioabsorbable polymeric material (polyglycolic acid/lactide copolymer, PGLA), was developed to accelerate intra-aneurysmal clot organization and fibrosis. The purpose of this study was to evaluate the efficacy and safety of the PGLA-coated coils in patients with intracranial aneurysms and to compare the outcome with that of bare platinum coils.PATIENTS AND TECHNIQUES: Fifty-one patients harboring 56 intracranial aneurysms underwent endovascular embolization with the PGLA-coated coils. In the control group were 78 consecutive patients, harboring 87 aneurysms, who underwent coil embolization with bare platinum coils. The authors compared coil volume, packing attenuation, degree of occlusion of aneurysms, procedure-related complications, and follow-up results between the 2 groups.RESULTS: The PGLA-coil group showed comparable data regarding rate of total or near-total occlusion of the aneurysm, incidence procedure–related thromboembolism, and management outcome. Mean coil volume deployed and packing attenuation of the PGLA-coil group were significantly higher than those of the bare-coil group (P = .0026 and P < .0001, respectively). Radiologic follow-up evaluation revealed recanalization in 14 of 39 aneurysms (major recanalization in 5 [13%] and minor recanalization in 9 [23%]) among the PGLA-coil group and in 29 of 64 aneurysms (major recanalization in 9 [14%] and minor recanalization in 20 [31%]) among the bare-coil group.CONCLUSION: In this study, the incidence of recanalization was not different in aneurysms treated with PGLA-coated coils compared with historical controls treated with bare platinum coils.